2011
DOI: 10.1016/j.ausmj.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multiple Endorsements and Consumer–Celebrity Attachment on Attitude and Purchase Intention

Abstract: This study examines consumer–celebrity attachment within multiple endorsement situations. A 2 × 2 factorial design manipulates attachment strength to the celebrity and endorsement situation while controlling for celebrity attractiveness, familiarity and match-up. Results show strong attachment to a celebrity encourages positive attitude towards the advertisement and brand regardless of the number of endorsements. A significant interaction effect is found for purchase intention, suggesting that both attachment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 28 publications
5
86
0
9
Order By: Relevance
“…Thomson's (2006) research shows both brand attachment and relationship quality are indicators of the strength of a relational bond. Other research shows evidence to suggest that both attachment and relationship quality result in superior brand attitudes and purchase intentions (De Canniere et al, 2010;Ilicic and Webster, 2011). As research in psychology finds authenticity results in the formation of relationships and greater perceived relationship quality (Brunell et al, 2010), we propose both brand attachment and relationship quality moderate the effect of relational authenticity, with relational authenticity inducing more favourable brand attitudes and purchase intentions when consumers are strongly attached to the brand, trust the brand, are satisfied with the brand and are commitment to the brand.…”
Section: Theoretical Modelmentioning
confidence: 98%
“…Thomson's (2006) research shows both brand attachment and relationship quality are indicators of the strength of a relational bond. Other research shows evidence to suggest that both attachment and relationship quality result in superior brand attitudes and purchase intentions (De Canniere et al, 2010;Ilicic and Webster, 2011). As research in psychology finds authenticity results in the formation of relationships and greater perceived relationship quality (Brunell et al, 2010), we propose both brand attachment and relationship quality moderate the effect of relational authenticity, with relational authenticity inducing more favourable brand attitudes and purchase intentions when consumers are strongly attached to the brand, trust the brand, are satisfied with the brand and are commitment to the brand.…”
Section: Theoretical Modelmentioning
confidence: 98%
“…This phenomenon was already observed in the context of products and brands (Rice et al, 2012;Carrillat et al, 2013;Ilicic and Webster, 2011;Subhadip, 2012;Tripp et al, 1994;Kaikati, 1987;Mowen and Brown, 1981). If the celebrity endorser is careful in his or her statements of favoritism, the power of endorsement remains.…”
Section: Celebrity Endorsementmentioning
confidence: 96%
“…In Studies 3 and 4, it was also possible to identify the effects of congruence (Fleck et al, 2012;Batra and Homer, 2004) and celebrity overexposure (Ilicic and Webster, 2011;Subhadip, 2012). In both studies, it was once again possible to identify the influence of contextual factors on the endorsement, in a context of established celebrities endorsing aspiring celebrities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on celebrities, or human brands, pay little attention to the meanings derived from celebrity attributes or characteristics. Studies in psychology, psychiatry, media and marketing have identified that celebrities are closely linked to personal identity with individual's developing parasocial relationships with celebrities (Caughey, 1978;Horton and Wohl, 1956;Nunn and Biressi, 2010;Rubin and McHugh, 1987), and possessing varying levels of emotional attachment from mild curious interest to celebrity worship (Ilicic and Webster, 2011;McCutcheon et al, 2003;Reeves et al, 2012;Thomson, 2006). Movement of meaning from idolized celebrity to consumer occurs through the creation of consumer self-image (McCracken, 1989).…”
Section: 2mentioning
confidence: 99%